Joint-specific power contribution at increasing double poling intensities - Danielsen, J.; Sandbakk, O.; Ettema, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The double poling (DP) technique in cross-country (XC) skiing is a complex and dynamic whole-body movement. One DP cycle can be divided into a poling phase, where the propulsive forces are generated, followed by a retrieval phase, where the body is repositioned and mechanical (potential+kinetic) energy (ME) increases. Although it is known that dynamic upper body and leg work both are of high importance in DP, the specific role and relative contributions from the various upper and lower body joints and interaction with ME requires further examination. Therefore, the present study performed an inverse dynamics analysis to investigate the joint-specific power and ME contributions at low, moderate and high DP intensities in a double poling ergometer. Methods: Six male XC skiers (age 22±5 yrs, body mass 80.3±5.5 kg, VO2max 5.9±0.6 L/min) completed three 4-min submaximal stages at low, moderate and high intensities on a modified Concept2 SkiErg. All exercises were performed on a Kistler force platform and the SkiErg was equipped with aKistler force cell, while reflective markers (Qualisys motion capture) were positioned on anatomical landmarks. All data were collected and synchronized in the Qualysis system. By applying inverse dynamics, individual joint powers (ankle, knee, hip, shoulder and elbow) and ME were calculated for the poling and retrieval phase, and for the complete cycle. DeLeva (1996) was used for estimates of body segments mass and inertia. Results: Net DP power increased from low to high intensity (109±11, 170±20, and 215±31 W, p=<0,001). Relative to net DP power the upper body contribution were 27, 29, and 31%, while the lower body contribution were 39, 39, and 44% at low, moderate and high intensities. More specifically, the relative ankle, knee, hip, shoulder and elbow powers were within 4-6%, 3-4%, 32-35%, 21-27%, 4-6% respectively, and hardly affected by intensity. Movements in the pelvis and trunk were not differentiated in this study but may account for 25-30%. During poling most power was produced by the upper body (~37%) and by utilization of ME (50-60%) while some absorption took place in the lower body. The retrieval phase was characterized by positive power produced by the lower body (almost 100% of total joint power) and thus an increase in ME. Discussion: This study demonstrates that most power is produced in the body`s core (hip, shoulder and pelvis-trunk) during DP. Although the various segments have different roles in the poling and retrieval phase, the relative power produced during a whole cycle remains evenly distributed over upper and lower body and is unaffected by intensity. The exchange of joint power and ME is essential for the lower body`s contribution.